Between Euro-Federalism, Euro-Pragmatism and Euro-Populism: the Gaullist movement divided over Europe. (3rd April 2017) - Leruth, Benjamin; Startin, Nicholas
Abstract: Since the creation of the European Community, the Gaullist movement has never been united over the question of European integration. De Gaulle's intergovernmental vision of the European project has largely been the dominant discourse. At times however, this narrative has been questioned—on the one hand by more supranational notions of European integration; and on the other by a more pro-sovereignty Eurosceptic discourse. Subsequently, in its various modern-day guises the Gaullist movement has faced a series of major internal divisions with regard to its position on 'Europe'. This uncertainty has also manifested itself at the highest level as demonstrated by the changing discourse advocated by former French presidents Jacques Chirac and Nicolas Sarkozy. This paper analyses the internal tensions over the European issue within the Gaullist movement at elite level. It determines that despite Chirac's and Sarkozy's attempts to unite the party throughout their presidencies the Gaullist movement is far from having moved towards a united European stance. Accordingly, the authors identify that over the past three decades, it is possible to identify three distinct, and at times conflicting, Gaullist stances on European integration with which the party's elites have vacillated, namely Euro-Federalism, Euro-Pragmatism and Euro-Populism.